Time-course changes of field- and laboratory-based performance indicators in junior cyclists through a season - Revuelta, C.; Alejo, L. B.; Valenzuela, P. L.; Montalvo-Perez, A.; de la Calle, V.; Agundez, A.; Lucia, A.; Barranco-Gil, D. (International Journal of Sports Medicine, 2024)
This study aimed to assess the seasonal evolution of field-based and laboratory-based performance indicators in cyclists. Thirteen Junior male road cyclists (age 17.4±0.5 years) were followed up during a season, which was divided in three phases: early season (involving mainly training sessions), mid-season (including the first competitions), and late season (including the major competitions of the season). During each phase, field-based power output data were registered for the assessment of maximum mean power values, and laboratory-based endurance (ramp test and simulated 8-minute time trial), muscle strength/power (squat, lunge, hip thrust) and body composition indicators (dual-energy X-ray absorptiometry) were also assessed. A progressive (p<0.01) increase in maximum mean power values (e.g., 3.8±0.3 and 4.5±0.4 watts/kg in early and late season, respectively, for 60-minute efforts) and on 8-minute time trial performance (i.e., 5.3±0.3 and 5.6±0.4 watts/kg, respectively) was observed through the season. Yet, more "traditional" endurance indicators (i.e., ventilatory threshold, respiratory compensation point, or maximum oxygen uptake) seemed to show a ceiling effect beyond the mid-season. In addition, neither peak power output, body composition, nor muscle strength indicators followed a similar pattern to the aforementioned field-based indicators. In summary, in Junior cyclists field-based indicators seem more sensitive to monitor endurance cyclists` changes in actual fitness and performance capacity than more "traditional" laboratory-based markers in Junior cyclists.